Differentiation and Immunological Function of MDSC-Derived Dendritic Cells - Ding, Zequn; Zhang, Yan (Global Medical Genetics, 2022)
Dendritic cells (DCs) play a key role in initiating and regulating immune responses, and in addition to their roles in vivo, DCs are used as natural adjuvants for various tumor vaccines. In vitro, monocytes can be used to induce DCs, but in tumor patients, due to insufficient bone marrow hematopoiesis, extramedullary hematopoiesis and tumor-associated myeloid cells expand, and monocytes mainly exist in the form of myeloid-derived suppressor cells (MDSCs). The purpose of this experiment was to explore the differences in the differentiation and immune function of DCs induced by MDSCs in tumor patients. In a mouse model, we used normal mouse bone marrow cell-derived DCs as control cells, and in a tumor-bearing model, we induced MDSCs in the spleen to generate DCs (MDSC-DCs). Through flow cytometry, we found that the production of MDSC-DCs was significantly higher than that of control mice, and the secretion of interferon-γ of MDSC-DCs was significantly reduced. Through OVA antigen presentation experiments, we found that the antigen presentation ability of MDSC-DCs was significantly decreased. Through adoptive treatment of tumor-bearing mice cells, we found that the antitumor immune function of MDSC-DCs was significantly reduced. After that, we explored the mechanism of the decrease of immune function activity of MDSC-DCs. We determined that the surface markers of MDSC-DCs were changed by flow cytometry. Through flow sorting and RNA sequencing, we found that some pathways and key gene expression in MDSC-DCs were changed. In conclusion, this study found that the immune function of MDSC-DCs decreased and explored the mechanism of the decreased immune function activity.
Keywords: MDSC-DCs; BMDCs; antitumor activity